Replacement of dietary fish oil with increasing levels of linseed oil: Modification of flesh fatty acid compositions in Atlantic salmon (Salmo salar) using a fish oil finishing diet - Bell, J Gordon; Henderson, R James; Tocher, Douglas R; Sargent, John R (Lipids, 2004)
Five groups of Atlantic salmon smolts, of initial mean weight 127 ± 3g, were fed increasing levels of dietary linseed oil (LO) in a regression design. The control diet contained capelin oil (FO) only and the same oil was blended with LO to provide the experimental diets. After an initial growth period of 40 weeks all treatment groups were switched to a finishing diet containing only FO for a further 24 weeks. Growth, flesh total lipid content and astaxanthin content were not affected by dietary oil composition. The fatty acid compositions of flesh total lipids were linearly correlated with dietary fatty acid compositions (r2 = 0.88-1.00, P < 0.0001). Inclusion of the LO at 50% of added dietary lipid reduced flesh docosahexaenoic (22:6n-3; DHA) and eicosapentaenoic acids (20:5n-3; EPA) to 65 and 58%, respectively, of the concentrations in fish fed FO. When inclusion of dietary LO reached 100% the flesh DHA and EPA concentrations were reduced to 38 and 30%, respectively, of values in fish fed FO. Differences between diet fatty acid concentration and flesh fatty acid concentration showed that 16:0, 18:1n-9 and especially DHA were preferentially retained by salmon whereas 18:2n-6, 18:3n-3 and 22:1n-11 were selected against and presumably utilised for energy production. Feeding a finishing diet containing FO alone for 16 weeks restored flesh DHA and EPA concentrations in fish previously fed 50 and 100% LO to around 80% of their values in fish fed FO throughout. Flesh DHA and EPA concentrations in fish fed up to 50% LO were in excess of recommended intake values for these fatty acids. By utilising FO finishing diets for at least 16 weeks similar flesh DHA and EPA concentrations could be achieved in fish previously fed up to 100% LO for 40 weeks. This study suggests that LO can be used as a substitute for FO in salmon feeds during seawater growth and that any reductions in DHA and EPA can be overcome by feeding FO for a period before harvest.